2011
DOI: 10.1007/s00268-011-1203-7
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Strategies for Management of the Open Abdomen

Abstract: Since the mid-1990s the surgical community has seen a surge in the prevalence of open abdomens (OAs) reported in the surgical literature and in clinical practice. The OA has proven to be effective in decreasing mortality and immediate postoperative complications; however, it may come at the cost of delayed morbidity and the need for further surgical procedures. Indications for leaving the abdomen open have broadened to include damage control surgery, abdominal compartment syndrome, and abdominal sepsis. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
114
0
18

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(135 citation statements)
references
References 140 publications
(106 reference statements)
3
114
0
18
Order By: Relevance
“…2 A variety of different techniques for TAC have been used in the past, including the Bagota bag, mesh, Wittmann patch and Barker vacuum pack. A systematic review and prospective observational trial have demonstrated that the ABThera Open Abdomen Negative Pressure Therapy System (KCI USA) may be the most effective TAC method.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…2 A variety of different techniques for TAC have been used in the past, including the Bagota bag, mesh, Wittmann patch and Barker vacuum pack. A systematic review and prospective observational trial have demonstrated that the ABThera Open Abdomen Negative Pressure Therapy System (KCI USA) may be the most effective TAC method.…”
mentioning
confidence: 99%
“…The ABThera, when used alone, fails to reapproximate the fascia in about 30% of patients with an open abdomen. [2][3][4] Failure to close the fascia primarily results in an increased risk of enteroatmospheric fistula, requirement for skin grafting of the visceral mass and a large ventral hernia. Furthermore, early primary closure of the open abdomen has been associated with improved patient survival.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 The open abdomen procedure is a significant surgical advance, as part of damage control techniques in severe abdominal trauma. 15 Surgeons should be aware of the pathophysiology of severe intra-abdominal sepsis and always keep in mind the option of open abdomen in order to be able to use it in the right patient at the right time. However, the use of this technique has been described in very modern contests, but only few Authors relate about their experience in poor countries where human and technical resources are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Hemorrhagic shock and required crystalloid and blood product resuscitation result in visceral edema often preventing primary fascial closure of the abdominal wall [3]. As a result, definitive abdominal wall repair is preceded by a period of temporary abdominal wall closure [4] [5]. If early primary fascial closure is not practical or feasible, techniques have been reported for management of the open abdominal defect including closure with an absorbable mesh to provide a scaffold for visceral granulation tissue formation and cutaneous coverage by split-thickness skin graft (STSG) [6] [7].…”
Section: Introductionmentioning
confidence: 99%